Prehistoric people - Coville, B. Bruce Coville; McDermott, M. Michael McDermott (New York: Doubleday, 1990)
Traces the development of humans from Australopithecus to Cro-Magnon, focusing on methods of hunting and farming, artistic endeavors, religious rituals, and technological developments.
Includes index